Thriving psychological well-being in undergraduate nursing student: a grounded theory study with the life grid approach - Lu Zhou; Thitinan Chankoson; YuMing Wu; EnLi Cai (BMC, 2023)
Abstract Background Psychological well-being (PWB) plays a vital role in successful adaptation to the Bachelor of Nursing journey and affects career development. However, there is little known about the functional and social processes associated with enhancing well-being specific to the subjective perspective of nursing students. Aim To investigate how nursing students promote their psychological well-being to conceptualize thriving psychological well-being. Method This qualitative study analyzed and reviewed a life grid and semi-structured in-depth interviews of 20 Chinese Nursing graduates by investigators and participants, following Charmaz's constructivist grounded theory. The constant comparative method was used to analyze data. This study took place between 2020 and 2022. Results All participants experienced fluctuations in psychological well-being. This study identified a new understanding of how nursing students enhance their psychological well-being. Thriving awareness was co-constructed as the core category and based on the relationship with a supportive environment, the thriving psychological well-being of nursing students is conceptualized. Conclusions It is imperative to enhance the psychological counseling and support for nursing students during their clinical placements, during the period just entering university as well as after repeated outbreaks of COVID-19. Nursing educators and administrators could develop appropriate educational programs and interventions based on the theoretical model-Thriving psychological well-being.